Determinan agresivitas pajak pada perusahaan perbankan yang terdaftar di Bursa Efek Indonesia - Florensia, Carina; Budiantoro, Risanda Alirastra (Journal of Accounting and Digital Finance, 2025)
This study aims to examine the effect of profitability, thin capitalization, capital intensity, firm size, and independent commissioners on tax aggressiveness in banking companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Tax aggressiveness is measured using the Effective Tax Rate (ETR) as a proxy. The study employs a quantitative approach with panel data regression, involving 29 firms selected through purposive sampling. The Common Effect Model (CEM) is identified as the best-fitting model. The findings reveal that profitability and independent commissioners have a negative and significant impact on tax aggressiveness, while thin capitalization, capital intensity, and firm size show no significant effect. These results emphasize the importance of internal corporate governance, particularly the supervisory role of independent commissioners, in reducing tax avoidance behavior. Policy implications suggest the need for stronger tax oversight based on firm characteristics and the adoption of advanced technologies for early detection of avoidance practices. The study is limited to the banking sector; future research should expand across industries and consider broader governance variables.